Toward Sustainable Broiler Production: Evaluating Microbial Protein as Supplementation for Conventional Feed Proteins - Daniela-Mihaela Grigore; Maria-Luiza Mircea; Elena Narcisa Pogurschi (Agriculture, 2025)
The increasing demand for sustainable poultry production has urged the exploration of alternative feed strategies supporting animal performance and environmental goals. The first section outlines the protein requirements in broiler nutrition (19–25% crude protein) and the physiological importance of balanced amino acid profiles. Vegetal conventional protein sources are discussed in terms of their nutritional value (12.7–20.1 MJ/kg), limitations (antinutritional factors), and availability. Emerging trends in broiler nutrition highlight the integration of supplements and the need for innovative feed solutions as support for the improvement in broiler body weight and feed efficiency increase. Microbial protein sources: yeast biomass (41–60% of 100 g dry weight), microbial mixed cultures (32–76% of 100 g dry weight), and beer by-products, such as brewer’s spent yeast (43–52% of 100 g dry weight), offer promising nutritional profiles, rich in bioactive compounds (vitamin B complex, minerals, enzymes, and antioxidants), and may contribute to improved gut health, immunity, and feed efficiency when used as dietary supplements. The review also addresses the regulatory and safety considerations associated with the use of microbial protein in animal feed, emphasizing EU legislation and standards. Finally, recent findings on the impact of microbial protein supplementation on broiler growth performance, carcass traits, and overall health status are discussed. This review supports the inclusion of microbial protein sources as valuable co-nutrients that complement conventional feed proteins, contributing to more resilient and sustainable broiler production and broiler meat products.